1999
DOI: 10.4049/jimmunol.162.7.4277
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glycosylphosphatidyl Inositol-Anchored Protein on Human Leukocytes: A Possible Role for Regulation of Neutrophil Adherence and Migration

Abstract: We report here a novel glycosylphosphatidyl-inositol (GPI)-anchored glycoprotein on human leukocytes. Treatment of neutrophils with a mAb (3H9) to this molecule sequentially up-regulates and down-regulates β2 integrin-dependent adhesion of these cells as well as their transendothelial migration in vitro. In addition, this mAb simultaneously modulates the avidity of β2 integrin for its ligand, iC3b, with kinetics similar to those observed in 3H9 modulation of neutrophil adherence. This mAb also induces β2 integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…VNN 2 was detected high expression in kidney tissue [ 72 ]. The protein Gpi80, encoded by the VNN2, exhibited surface aggregation on activated migrating neutrophils and potentially modulated neutrophil adhesion and migration [ 73 ]. Thus, we implied that genus Marvinbryantia involved in pathological exacerbation of DN by inflammation activation.…”
Section: Discussionmentioning
confidence: 99%
“…VNN 2 was detected high expression in kidney tissue [ 72 ]. The protein Gpi80, encoded by the VNN2, exhibited surface aggregation on activated migrating neutrophils and potentially modulated neutrophil adhesion and migration [ 73 ]. Thus, we implied that genus Marvinbryantia involved in pathological exacerbation of DN by inflammation activation.…”
Section: Discussionmentioning
confidence: 99%
“…This novel protein GPI‐80 and Vanin‐1, a GPI‐anchored protein expressed on perivascular thymic stromal cells, have been found 40% homologous with human biotinidase. This report suggested that a biotinidase superfamily of molecules may regulate leukocyte trafficking along the endothelium toward the extravascular tissues (22).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired immunoregulatory function or immunodeficiency has occurred in children with biotinresponsive multiple carboxylase deficiency (20,21). However, a novel glycosylphosphatidylinositol-anchored protein (GPI-80) has been described on human leukocytes (22). This novel protein GPI-80 and Vanin-1, a GPI-anchored protein expressed on perivascular thymic stromal cells, have been found 40% homologous with human biotinidase.…”
Section: Discussionmentioning
confidence: 99%